Treatment strategies for DNA repair-deficient prostate cancer - Teply, Benjamin A. (Expert Rev Clin Pharmacol, 2017)
INTRODUCTION: Common recurrent genetic alterations have been identified in prostate cancer through comprehensive sequencing efforts, and the prevalence of mutations in DNA repair pathway genes in patients with advanced and metastatic disease approaches 20–25%. Identification of these underlying DNA repair defects may present unique treatment opportunities for patients, both in terms of standard-of-care treatments and selected investigational agents. AREAS COVERED: We review our current understanding of the genomic landscape of prostate cancer, with special attention to alterations in DNA repair pathway genes in metastatic castration-resistant disease. For patients with tumors deficient in homologous recombination repair, potential opportunities for treatment include platinum chemotherapy, poly(ADP) ribose polymerase (PARP) inhibitors, bipolar androgen therapy, and maybe immune checkpoint blockade therapy. In addition, tumors with mismatch repair defects (i.e. microsatellite instability) may be particularly susceptible to checkpoint blockade immunotherapy. EXPERT COMMENTARY: We anticipate that genomic profiling of tumors will become necessary to guide treatment of advanced prostate cancer treatment in the coming years. Work is needed to define the optimal tissue to test, and to define the national history of tumors with specific genetic defects. The prognostic and therapeutic importance of germline vs somatic DNA repair alterations, and mono-allelic vs bi-allelic inactivation, also remains unclear. Finally, optimal strategies to sequence or combine targeted agents for these patients with ‘actionable’ mutations are now needed.